2015
DOI: 10.1007/s11120-015-0101-5
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of specific plastid ribosomal proteins suppresses thf1 leaf variegation, implying a role of THF1 in plastid gene expression

Abstract: Chloroplast development is regulated by many biological processes. However, these processes are not fully understood. Leaf variegation mutants have been used as powerful models to elucidate the genetic network of chloroplast development since the degree of leaf variegation is regulated by developmental and environmental cues. The thylakoid formation 1 (thf1) mutant is unique for its variegation in both leaves and cotyledons. Here, we reported a new suppressor gene of thf1 leaf variegation, designated sot8. Map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 36 publications
(62 reference statements)
1
22
0
Order By: Relevance
“…SIG6 is a plastid transcription factor specifically controlling gene expression through the plastid-encoded RNA polymerase and the mutation of SIG6 suppresses thf1 variegation (Hu et al 2015). Genetic screening for the second-site suppressor lines of thf1 and var2 suggested that the reduced rate of plastid protein biosynthesis is important for chloroplast development in variegated leaves (Ma et al 2015b).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…SIG6 is a plastid transcription factor specifically controlling gene expression through the plastid-encoded RNA polymerase and the mutation of SIG6 suppresses thf1 variegation (Hu et al 2015). Genetic screening for the second-site suppressor lines of thf1 and var2 suggested that the reduced rate of plastid protein biosynthesis is important for chloroplast development in variegated leaves (Ma et al 2015b).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…2), are detected in the green but not the white leaf areas, specifically in the chloroplasts, of the var2 mutant grown even under normal light conditions, indicative of its persistent photooxidative stress (Kato et al, 2009). A series of genetic studies in Arabidopsis identified trans-acting factors suppressing var1/var2 leaf variegation; these included Clp subunits, translation factors, a pentatricopeptide repeat protein, a pseudouridine synthase homolog, a plastid transcriptionally active chromosome component, a prokaryotic-like peptide deformylase, ribosomal proteins, circularly permuted GTPase family proteins, and a sigma factor Miura et al, 2007;Yu et al, 2008Yu et al, , 2011Liu et al, 2010aLiu et al, , 2010bLiu et al, , 2013Adam et al, 2011;Wu et al, 2013;Powikrowska et al, 2014;Hu et al, 2015;Ma et al, 2015;Qi et al, 2016). Several models have been proposed to explain leaf variegation suppression, but the precise mechanism remains elusive (Miura et al, 2007;Yu et al, 2008).…”
Section: Ftshmentioning
confidence: 99%
“…THF1 has been suggested to be a subunit of PSII and also involved in the plasma membrane G-protein-mediated sugar signaling (Keren et al, 2005;Huang et al, 2006). Interestingly, var2 and thf1 share many similar genetic suppressor loci, including genes for chloroplast Clp protease complexes and chloroplast ribosomal proteins, suggesting a functional relationship between these two proteins (Yu et al, 2008;Liu et al, 2013;Wu et al, 2013;Ma et al, 2015).…”
mentioning
confidence: 99%